Methicillin-resistant coagulase-positive staphylococci in new, middle-aged, and old veterinary hospitals in southern Thailand: A preliminary study - Tanawan Soimala; Siriwat Wasiksiri; Kanpapat Boonchuay; Tuempong Wongtawan; Punpichaya Fungwithaya (Veterinary World, 2024)
Background and Aim: Methicillin-resistant coagulase-positive staphylococci (MRCoPS) cause pyoderma, dermatitis, and nosocomial infection. Numerous factors, including indiscriminate antimicrobial use (AMU) in veterinary medicine, cleaning practices, and AMU in hospitals, contribute to MRCoPS. However, the relationship between hospital age and MRCoPS has not yet been investigated. This study aimed to estimate the prevalence of MRCoPS in the treatment and operation rooms of new, middle-aged, and old veterinary hospitals. Materials and Methods: automated system was then used to determine the minimum inhibitory concentration. Results: gene. Interestingly, more MRCoPS was found in new hospitals (six isolates) than in middle-aged (one isolate) and old hospitals (two isolates), although there was no statistically significant difference in the presence of MRCoPS across new, middle-aged, and old veterinary hospitals (p = 0.095), Kruskal-Wallis test. There is a need for further detailed studies, including an increase in the number of hospitals in various locations. Conclusion: MRCoPS is a nosocomial pathogen that causes zoonotic and recurrent infections in veterinary hospitals. The prevalence of MRCoPS tended to be higher in new hospitals. Areas with heavy animal contact, such as hospital floors, are areas of particular concern, and cleaning/disinfection of these areas must be highlighted in hygiene regimens.
Keywords: Antimicrobial Resistance in Staphylococcus; Surgical site infection prevention; Streptococcal Infections and Treatments